Advance on flexible pressure sensors based on metal and carbonaceous nanomaterial. (September 2021) - Liu, Meng-Yang; Hang, Cheng-Zhou; Zhao, Xue-Feng; Zhu, Li-Yuan; Ma, Ru-Guang; Wang, Jia-Cheng; Lu, Hong-Liang; Zhang, David Wei
Abstract: As an indispensable and prevailing kind of flexible sensors, pressure sensors have been extensively used in the field of flexible electronics. To enhance the performance and broaden the applications of flexible pressure sensors, emerging nanomaterials with excellent electromechanical properties have been explored and developed over recent years. Herein, the latest progresses in flexible pressure sensors based on metal and carbonaceous nanomaterial are reviewed in this paper. Firstly, fundamental considerations of pressure sensors including transduction principles, evaluation parameters and nano-micro structures are presented. Furthermore, flexible pressure sensors based on carbonaceous nanomaterials, transition metal carbides and carbonitrides (Mxene), along with metal nanomaterials are reviewed and classified by different transduction principles. At last, a number of applications on electronic skin (E-skin) involving metal and carbonaceous nanomaterial-based flexible pressure sensors are introduced, including pressure distribution sensing, force direction detection, multifunctional sensing and system integration. Graphical Abstract: ga1 Highlights: Latest progresses on flexible pressure sensors based on metal and carbonaceous nanomaterials are reviewed elaborately. Fundamental consideration, device structure, and E-skin application of nanomaterial-based pressure sensors are summarized. This review should have considerable reference value for design, fabrication and development of flexible pressure sensors.